Assessing the impacts of IPsec cryptographic algorithms on a virtual network embedding problem. (October 2018) - Camilo, Bernardo C.V.; Couto, Rodrigo S.; Costa, Luís Henrique M.K.
Highlights: IPsec overheads can have a major influence in a virtual network embedding problem. When using IPsec, the CPU overhead is much greater than the bandwidth overhead. Although small, the bandwidth overhead of IPsec should not be neglected. Abstract: Network virtualization has emerged as an alternative to traditional networking, allowing several different virtual networks to operate on the same physical infrastructure. Despite its wide adoption, virtualization still has some open issues. One of the challenges is related to resource allocation of virtual networks on the physical substrate. In the literature, this problem is known as virtual network embedding. Different papers propose virtual network embedding considering different aspects, but only a few address security, which is a key requirement for many applications. This work quantifies the overhead of cryptographic algorithms in order to use them in virtual network embedding solutions. Both theoretical and experimental evaluation of IPsec algorithms are conducted. The obtained results are applied to a known virtual network embedding problem, using realistic characteristics. These results demonstrate the importance of considering such overheads to perform the allocation of secure virtual networks.